Method for preparing vinyl chloride-based polymer, and vinyl chloride-based polymer prepared thereby

By using highly hydrated polyvinyl acetate, cellulose dispersant and carbonate salt during the PVC resin polymerization process, the problems of low melting rate and density trade-off of PVC resin are solved, and PVC resin production with high mechanical strength and high production efficiency is achieved.

JP2025019278AActive Publication Date: 2025-02-06LG CHEM LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024206187
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-07-01
Filing Date
2024-11-27
Publication Date
2025-02-06
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

The existing PVC resin has low melting rate during processing, resulting in incomplete dissolution of the chain structure, forming unsolated particles, affecting mechanical properties. At the same time, there is a trade-off relationship between high CPA and high density, making it difficult to take into account both mechanical strength and production efficiency.

Method used

Using the method of mixing dispersant and carbonate metal salt, high-hydrated polyvinyl acetate and cellulose dispersant, the amount of dispersant and carbonate salt is controlled, the polymerization reaction conditions are optimized, and the melting rate and density balance are improved.

Benefits of technology

PVC resin with high CPA and low residual monomer content is produced, with high mechanical strength and high production efficiency, and the particle shape is close to spherical and the melting rate is fast.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019278000001
    Figure 2025019278000001
  • Figure 2025019278000002
    Figure 2025019278000002
  • Figure 2025019278000003
    Figure 2025019278000003
Patent Text Reader

Abstract

To provide: a method for preparing a vinyl chloride-based polymer that can have excellent balance between the CPA and the bulk density of the vinyl chloride-based polymer while reducing the content of an unreacted monomer remaining in a final product; and a vinyl chloride-based polymer prepared by the preparation method.SOLUTION: The present invention relates to: a method for enabling preparation of a vinyl chloride-based polymer showing improved melting rate and mechanical properties and low harmfulness, by pre-mixing and injecting a mixed dispersant comprising polyvinyl alcohol of high hydration and a carbonate metal salt before polymerization, and then polymerizing a vinyl chloride-based monomer; and a vinyl chloride-based polymer prepared by the method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0086440 filed on July 1, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a method for producing a vinyl chloride polymer, which has a high melting rate, a low content of residual unreacted monomers, and a high bulk density of the polymer, by using a certain amount of a mixed dispersant containing a highly hydrated dispersant and a carbonate metal salt, and a vinyl chloride polymer produced by the method. [Background technology]

[0003] PVC is a representative thermoplastic resin that is inexpensive, has easy-to-control hardness, and has excellent physicochemical properties such as mechanical strength, weather resistance, and chemical resistance, and is used in a wide range of product areas such as films, sheets, and molded products.

[0004] In order to process PVC resin into a final product, it is necessary to mix the PVC resin with additives appropriate for the characteristics required for each product field and then extrude it. In this case, the faster the PVC resin mixture melts, the easier it is for the chain structure of the vinyl chloride polymer to dissolve and form stronger bonds with each other, which improves the mechanical properties of the final product. On the other hand, if the melting speed is low and the chain structure is not sufficiently dissolved, ungelled particles are formed during this process, and the formed ungelled particles act as defects in the final product and reduce the mechanical properties. Therefore, in product fields that require high mechanical strength, PVC resins with faster melting speeds are required.

[0005] Meanwhile, CPA (Cold Plasticizer Absorption) is a main physical property that indicates the characteristics of PVC resin, and the higher the CPA, the faster the melting speed. However, the CPA is in a trade-off relationship with the bulk density of the vinyl chloride polymer, and the higher the bulk density of the vinyl chloride polymer, the higher the extrusion amount during extrusion processing, resulting in superior productivity. That is, in order to produce a PVC resin with excellent mechanical strength, the higher the CPA of the PVC resin is, the lower the bulk density is, resulting in a problem of reduced productivity during processing. Therefore, research is needed on a method for producing a PVC resin with a good balance between CPA and bulk density in order to achieve an appropriate level of productivity and mechanical strength. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] KR10-2021-0034418A [Patent Document 2] KR10-2017-0124959A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a method for producing a vinyl chloride polymer, which can reduce the content of unreacted monomers remaining in a final product while achieving an excellent balance between the CPA and bulk density of the vinyl chloride polymer, and a vinyl chloride polymer produced by the method. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a method for producing a vinyl chloride polymer and a vinyl chloride polymer. (1) The present invention provides a method for producing a vinyl chloride polymer, comprising: a step (S1) of feeding a mixed dispersant and a carbonate metal salt into a polymerization reactor; and a step (S2) of polymerizing a vinyl chloride monomer in the presence of the mixed dispersant and the carbonate metal salt, wherein the mixed dispersant contains a highly hydrated polyvinyl alcohol having a hydration degree of 80 mol % or more, and the content of the highly hydrated polyvinyl alcohol in the mixed dispersant is 50 to 60 wt %.

[0009] (2) The present invention provides the method for producing a vinyl chloride polymer according to the above (1), wherein the mixed dispersant and the carbonate metal salt are mixed in advance and then charged into a polymerization reactor.

[0010] (3) The present invention provides a method for producing a vinyl chloride polymer according to the above (1) or (2), wherein the mixed dispersant further contains a low-hydration polyvinyl alcohol having a hydration degree of less than 80 mol % and a cellulose-based dispersant.

[0011] (4) The present invention provides the method for producing a vinyl chloride polymer according to any one of (1) to (3) above, wherein the cellulose-based dispersant is one or more selected from the group consisting of methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.

[0012] (5) The present invention provides the method for producing a vinyl chloride polymer according to any one of (1) to (4) above, wherein the carbonate metal salt is one or more selected from the group consisting of sodium carbonate (NaCO), potassium carbonate (KCO), and sodium hydrogen carbonate (NaHCO).

[0013] (6) The present invention provides the method for producing a vinyl chloride polymer according to any one of (1) to (5) above, wherein the mixed dispersant is used in an amount of 0.05 to 0.15 parts by weight based on 100 parts by weight of the vinyl chloride monomer.

[0014] (7) The present invention provides the method for producing a vinyl chloride polymer according to any one of (1) to (6) above, wherein the carbonate metal salt is used in an amount of 0.01 to 0.03 parts by weight based on 100 parts by weight of the vinyl chloride monomer.

[0015] (8) The present invention provides the method for producing a vinyl chloride polymer according to any one of (1) to (7) above, wherein the polymerization is carried out at 50 to 65° C.

[0016] (9) The present invention provides a vinyl chloride polymer, the content of which in a surface layer is 50% or more as measured by XPS analysis.

[0017] (10) The present invention provides the vinyl chloride polymer according to (9) above, which has a CPA (cold plasticizer absorption) of 18% or more.

[0018] (11) The present invention provides a granular material having a bulk density of 0.580 g / cm 3 The present invention provides a vinyl chloride polymer as described in (9) or (10) above, characterized in that:

[0019] (12) The present invention provides the vinyl chloride polymer according to any one of (9) to (11) above, which is in the form of spherical particles. Effect of the Invention

[0020] The vinyl chloride polymer produced by the production method of the present invention simultaneously exhibits high CPA and bulk density, is excellent in both productivity during extrusion processing and mechanical strength during production of the final product, has a low content of unreacted monomers, and is non-hazardous. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will now be described in more detail. The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0022] Meanwhile, the term "vinyl chloride polymer" as used herein collectively refers to a compound produced by polymerizing a vinyl chloride monomer, i.e., a vinyl chloride monomer alone or a mixture of a vinyl chloride monomer and a vinyl monomer capable of copolymerizing with the vinyl chloride monomer, and may refer to a polymer chain derived from a vinyl chloride monomer.

[0023] Method for producing vinyl chloride polymer The present invention provides a method for producing a vinyl chloride polymer, comprising: a step (S1) of feeding a mixed dispersant and a carbonate metal salt into a polymerization reactor; and a step (S2) of polymerizing a vinyl chloride monomer in the presence of the mixed dispersant and the carbonate metal salt, wherein the mixed dispersant contains a highly hydrated polyvinyl alcohol having a hydration degree of 80 mol % or more, and the content of the highly hydrated polyvinyl alcohol in the mixed dispersant is 50 to 60 wt %.

[0024] As mentioned above, the CPA and bulk density of vinyl chloride polymers are in a trade-off relationship, and in order to maintain mechanical strength and extrusion productivity at an appropriate level, it is necessary to find an appropriate balance between the CPA and bulk density of vinyl chloride polymers. As a result of research conducted for this purpose, the inventors of the present invention found that when a mixed dispersant containing a highly hydrated polyvinyl alcohol and a carbonate metal salt are mixed in advance and then vinyl chloride monomer is polymerized in the presence of the mixture, the CPA of the vinyl chloride polymer can be increased without impairing the bulk density, while the amount of unreacted monomer remaining in the final polymer can be reduced, and thus the method for producing vinyl chloride polymers of the present invention has been completed.

[0025] Each step of the process for producing a vinyl chloride polymer of the present invention will now be described. Step of adding mixed dispersant and carbonate metal salt (S1) The production method of the present invention includes a step (S1) of introducing a mixed dispersant and a carbonate metal salt into a polymerization reactor before carrying out a polymerization reaction.

[0026] The mixed dispersant used in this step serves to disperse the vinyl chloride monomer to be added in the following step in the solvent, and may be a mixture of two or more different dispersants, and at least one of the two or more dispersants contained in the mixed dispersant may be a high hydration polyvinyl alcohol having a hydration degree of 80 mol% or more. Particularly preferably, the high hydration polyvinyl alcohol may have a hydration degree of 85 mol% or more. When such a polyvinyl alcohol having a high hydration degree is mixed with another dispersant, there is an advantage that the stability of the final product particles can be further improved. Meanwhile, the polyvinyl alcohol used as the dispersant in this step is in the form of polyvinyl acetate hydrated to replace a part of the acetate with alcohol, and the hydration degree is defined as the degree of substitution of the acetate with alcohol.

[0027] The content of the highly hydrated polyvinyl alcohol in the mixed dispersant may be 50 to 60% by weight. If the content of the highly hydrated polyvinyl alcohol in the mixed dispersant is too low, the stability of the particles decreases during the polymerization process, causing a large amount of scale to be generated, and vinyl chloride polymer particles cannot be obtained in a uniform shape. Furthermore, the bulk density of the vinyl chloride polymer finally produced is too low, which may cause a problem of reduced extrusion rate. On the other hand, if the content of the highly hydrated polyvinyl alcohol in the mixed dispersant is too high, the voids inside the vinyl chloride polymer particles obtained may decrease, resulting in a low plasticizer absorption rate, and therefore the residual monomers may not be smoothly discharged into the atmosphere, causing a rapid increase in the content of unreacted monomers remaining in the final product.

[0028] The mixed dispersant may further contain a low hydration polyvinyl alcohol of less than 80 mol% and a cellulose-based dispersant in addition to the high hydration polyvinyl alcohol described above. When high hydration polyvinyl alcohol and low hydration polyvinyl alcohol are used together, basic physical properties such as polymer particle size and plasticizer absorption rate can be easily controlled, and polymer particles with relatively fast melting properties can be obtained while satisfying basic physical properties required for products because the skin layer is not too thick. The hydration degree of the low hydration polyvinyl alcohol may be less than 80 mol%, preferably 50 to 75 mol%, and the low hydration polyvinyl alcohol may contain two or more polyvinyl alcohols having hydration degrees within the above-mentioned range.

[0029] The mixed dispersant may be used in an amount of 0.05 to 0.15 parts by weight, preferably 0.08 to 0.12 parts by weight, based on 100 parts by weight of the vinyl chloride monomer. If the amount of the mixed dispersant used is too small, the mixed dispersant may not function sufficiently and polymerization stability may decrease, and if the amount of the mixed dispersant used is too large, dispersant components may remain and act as impurities in the final product, adversely affecting the quality of the product.

[0030] The cellulose-based dispersant may act as a protective colloid auxiliary to stabilize the reactants during the polymerization process. The cellulose-based dispersant may be one or more selected from the group consisting of methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.

[0031] The carbonate-based metal salt used in this step acts as a pH adjuster and can reduce the content of unreacted monomers that may remain in the final product. As the carbonate-based metal salt, one that can be dissolved in water and ionized may be used, and specifically, one or more selected from the group consisting of sodium carbonate (Na2CO3), potassium carbonate (K2CO3), and sodium bicarbonate (NaHCO3) may be used.

[0032] The carbonate metal salt may be used in an amount of 0.01 to 0.03 parts by weight, preferably 0.015 to 0.025 parts by weight, based on 100 parts by weight of the vinyl chloride monomer. If the amount of the carbonate metal salt used is too small, the carbonate metal salt may not perform its role sufficiently, and if the amount of the carbonate metal salt used is too large, the carbonate metal salt component may affect the dispersant, reducing the dispersion stability, and thus the size of the polymer particles may become excessively large.

[0033] Meanwhile, in this step, the mixed dispersant and the carbonate metal salt may be premixed and then added to the polymerization reactor. By premixing and adding the mixed dispersant and the carbonate metal salt before the start of the polymerization reaction, rather than adding them after the start of the polymerization reaction, the content of the vinyl chloride polymer in the surface layer of the final product can be further increased, thereby increasing the melting rate.

[0034] Polymerization step (S2) As described above, the polymerization reaction can be carried out by adding the mixed dispersant and the carbonate metal salt to the polymerization reactor, and then adding the vinyl chloride monomer. In particular, the polymerization reaction in this step can be carried out by a suspension polymerization method.

[0035] The vinyl chloride monomer may be one of vinyl chloride monomers, or may be a mixed monomer containing a vinyl chloride monomer and a vinyl monomer capable of copolymerizing with the vinyl chloride monomer. The mixed monomer may contain 1 to 50 parts by weight of a copolymerizable vinyl monomer based on 100 parts by weight of the vinyl chloride monomer. When the copolymerizable vinyl monomer is contained within the above range, there is an advantage that the suspension polymerization is stably performed while the processability of the final vinyl chloride polymer is excellent. The vinyl monomer may be one or more selected from the group consisting of olefin compounds such as ethylene and propylene; vinyl esters such as vinyl acetate and vinyl propionate; unsaturated nitriles such as acrylonitrile; vinyl alkyl ethers such as vinyl methyl ether and vinyl ethyl ether; unsaturated fatty acids such as acrylic acid, methacrylic acid, itaconic acid, and maleic acid; and anhydrides of these fatty acids.

[0036] In this step, a solvent for suspension polymerization may be used, and the solvent may be deionized water. The amount of the solvent may be appropriately adjusted depending on the size of the polymerization reactor and the amount of the monomer used, and may be, for example, 70 parts by weight or more per 100 parts by weight of the vinyl chloride monomer. The solvent may be mixed with the mixed dispersant and the carbonate metal salt in the previous S1 step and then charged.

[0037] In this step, a polymerization initiator for starting the polymerization reaction may be used. The polymerization initiator may be used in an amount of 0.02 to 0.2 parts by weight relative to 100 parts by weight of the vinyl chloride monomer to be polymerized. If the polymerization initiator is used in an amount of less than 0.02 parts by weight, the polymerization reaction time may be prolonged, the conversion rate to the vinyl chloride polymer may be reduced, and the productivity may be reduced. If the polymerization initiator is used in an amount of more than 0.2 parts by weight, the polymerization initiator cannot be completely consumed during the polymerization process, and may remain in the vinyl chloride polymer slurry finally produced, thereby reducing the thermal stability, etc. More specifically, the polymerization initiator may be used in an amount of 0.04 to 0.12 parts by weight relative to 100 parts by weight of the vinyl chloride monomer.

[0038] Specific examples of the polymerization initiator include peroxide compounds such as dicumyl peroxide, dipentyl peroxide, di-3,5,5-trimethylhexanoyl peroxide, and dilauryl peroxide; peroxydicarbonate compounds such as diisopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, and di-2-ethylhexyl peroxydicarbonate; peroxyester compounds such as t-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, and t-butyl peroxyneodecanoate; azo compounds such as azobis-2,4-dimethylvaleronitrile; hydroperoxide compounds such as t-butyl hydroperoxide; and sulfate compounds such as potassium persulfate and ammonium persulfate. Any one or a mixture of two or more of these may be used.

[0039] In this step, the polymerization may be carried out at a temperature of 50 to 65°C, more specifically, at a temperature of 50 to 60°C. Since the polymerization reaction of vinyl chloride polymer is an exothermic reaction, a heat removal process may be carried out through a reactor jacket and a reflux condenser (R / CN) to minimize temperature changes during the polymerization process. When the polymerization reaction is carried out at a temperature in this range, foam generation is prevented, while repolymerization and scale generation can be suppressed. In addition, decomposition of the polymerization initiator remaining at the end of the reaction is induced in this temperature range, and a vinyl chloride polymer having better physical properties after the reaction can be produced.

[0040] In this step, additives such as antioxidants, bases, crosslinking agents, polymerization regulators, chain transfer agents, antistatic agents, scale inhibitors, surfactants, etc. may be further added, and the types and contents of the additives are not particularly limited and may be of the usual types and contents known in the art. The additives may be added at any time during the polymerization process, and may be added all at once or continuously.

[0041] Vinyl chloride polymer The present invention provides a vinyl chloride polymer that can be produced by the above-mentioned method for producing a vinyl chloride polymer. Specifically, the present invention provides a vinyl chloride polymer having a vinyl chloride polymer content of 50% or more in a surface layer as measured by XPS analysis.

[0042] When vinyl chloride polymers are produced by suspension polymerization, the final product is obtained in a form in which the vinyl chloride polymer exists inside and the surface is surrounded by a dispersant. In this case, the band forming the surface is called a skin layer, and generally, the thicker the skin layer, the slower the melting speed, and therefore the melting time tends to increase. The thickness of such a skin layer can be inferred from the content of vinyl chloride polymer in the surface obtained by XPS analysis of the surface of the obtained polymer particles, and specifically, the lower the content of vinyl chloride polymer in the surface, the thinner the skin layer is evaluated to be.

[0043] In relation to this, when the above-mentioned method for producing a vinyl chloride polymer of the present invention is used, the content of dispersant on the polymer particle surface is reduced, the content of vinyl chloride polymer is increased, and a vinyl chloride polymer having a thin skin layer can be obtained. Specifically, when the production method of the present invention is used, a vinyl chloride polymer having a vinyl chloride polymer content of 50% or more in the surface layer can be obtained. The vinyl chloride polymer of the present invention has a thin skin layer, which allows the melting speed to be increased.

[0044] The content of the vinyl chloride polymer in the surface layer can be measured by the following method using XPS analysis. 1) Assume that the only materials that make up the surface of vinyl chloride polymers are PVC, PVA, and PVAc.

[0045] 2) Using PVC produced by bulk polymerization without using a dispersant, calculate the relative ratio of C element to Cl element in PVC particles (C:Cl=2.17:1). Since PVC produced by bulk polymerization consists of only PVC, the relative ratio calculated above is the relative ratio of C element to Cl element in pure PVC. Next, use the calculated relative ratio to back-calculate the PVC content from the Cl content measured in the surface layer of the target vinyl chloride polymer.

[0046] 3) The content of PVAc is calculated using the specific BE value appearing in the carbonyl peak present in PVAc in the C peak. 4) The C peak remaining after subtracting the contents of PVC and PVAc from the total content is determined to be the PVA content.

[0047] 5) The content of PVC based on the total content of PVC, PVA, and PVAc calculated by the above process (PVC / (PVC+PVA+PVAc))*100% is defined as the content of vinyl chloride polymer.

[0048] As the XPS equipment used for the above measurement, a normal equipment, for example, K-ALPHA+ (manufacturer: Thermofisher) may be used.

[0049] Furthermore, the vinyl chloride polymer of the present invention may have a CPA (cold plasticizer absorption) of 18% or more. Specifically, the vinyl chloride polymer of the present invention has a thin skin layer and a high melting rate, and accordingly the CPA can be as high as 18% or more. In addition, the vinyl chloride polymer of the present invention has a bulk density of 0.580 g / cm. 3 Although there is a trade-off between bulk density and CPA, the vinyl chloride polymer particles of the present invention have a shape that is relatively closer to a sphere than vinyl chloride polymers produced by existing methods, and therefore can exhibit a high bulk density in addition to a high CPA. The vinyl chloride polymer of the present invention may be in the form of spherical particles, particularly specifically, spherical particles having an aspect ratio of 1 to 1.2.

[0050] In the following, preferred examples are presented to aid in understanding the present invention, but the following examples are merely for the purpose of illustrating the present invention and are not intended to limit the scope of the present invention.

[0051] Example 1 Internal volume of 1 m with reflux condenser and stirrer 3 Into a stainless steel polymerization reactor, 130 parts by weight of polymerization water, 0.02 parts by weight of sodium carbonate, 0.055 parts by weight of polyvinyl alcohol with a hydration degree of 88 mol%, 0.025 parts by weight of polyvinyl alcohol with a hydration degree of 72 mol%, 0.009 parts by weight of polyvinyl alcohol with a hydration degree of 55 mol%, 0.011 parts by weight of hydroxypropyl methylcellulose, and 0.088 parts by weight of t-butyl peroxy neodecanoate (BND) were added, and the inside was degassed with a vacuum pump while stirring. Then, 100 parts by weight of vinyl chloride monomer was added, and the reaction was allowed to proceed while maintaining the temperature inside the polymerization reactor at 57.2°C. During the polymerization reaction, the pressure inside the reactor was reduced to 1.0 kg / cm. 2 When the temperature dropped, the polymerization was stopped, and 0.05 parts by weight of triethylene glycol-bis-[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate] was added as an antioxidant. After that, the unreacted monomer was recovered, and the resin slurry was recovered in the polymerization reactor.

[0052] Example 2 The same procedure was carried out as in Example 1, except that 0.050 parts by weight of polyvinyl alcohol having a hydration degree of 88 mol%, 0.028 parts by weight of polyvinyl alcohol having a hydration degree of 72 mol%, 0.010 parts by weight of polyvinyl alcohol having a hydration degree of 55 mol%, and 0.012 parts by weight of hydroxypropyl methylcellulose were used as the polyvinyl alcohol, to obtain a resin slurry.

[0053] Example 3 The same procedure was carried out as in Example 1, except that 0.06 parts by weight of polyvinyl alcohol having a hydration degree of 88 mol%, 0.022 parts by weight of polyvinyl alcohol having a hydration degree of 72 mol%, 0.008 parts by weight of polyvinyl alcohol having a hydration degree of 55 mol%, and 0.010 parts by weight of hydroxypropyl methylcellulose were used as the polyvinyl alcohol, to obtain a resin slurry.

[0054] Comparative Example 1 The same procedure as in Example 1 was carried out, except that sodium carbonate was not added, to obtain a resin slurry.

[0055] Comparative Example 2 The same procedure was carried out as in Example 1, except that sodium carbonate was not added, and 0.045 parts by weight of polyvinyl alcohol having a hydration degree of 88 mol%, 0.037 parts by weight of polyvinyl alcohol having a hydration degree of 72 mol%, 0.008 parts by weight of polyvinyl alcohol having a hydration degree of 55 mol%, and 0.010 parts by weight of hydroxypropyl methylcellulose were added, to obtain a resin slurry.

[0056] Comparative Example 3 The same procedure as in Example 1 was carried out, except that sodium carbonate was added after the monomer was added, to obtain a resin slurry.

[0057] Comparative Example 4 The same procedure as in Example 2 was carried out, except that sodium carbonate was added after the monomer was added, to obtain a resin slurry.

[0058] Comparative Example 5 The same procedure as in Example 3 was carried out, except that sodium carbonate was added after the addition of the monomer, to obtain a resin slurry.

[0059] Comparative Example 6 The same procedure was carried out as in Example 1, except that 0.045 parts by weight of polyvinyl alcohol having a hydration degree of 88 mol%, 0.037 parts by weight of polyvinyl alcohol having a hydration degree of 72 mol%, 0.008 parts by weight of polyvinyl alcohol having a hydration degree of 55 mol%, and 0.010 parts by weight of hydroxypropyl methylcellulose were added, to obtain a resin slurry.

[0060] Comparative Example 7 The same procedure was carried out as in Example 1, except that 0.065 parts by weight of polyvinyl alcohol having a hydration degree of 88 mol%, 0.020 parts by weight of polyvinyl alcohol having a hydration degree of 72 mol%, 0.008 parts by weight of polyvinyl alcohol having a hydration degree of 55 mol%, and 0.007 parts by weight of hydroxypropyl methylcellulose were added to obtain a resin slurry. The content of highly hydrated polyvinyl alcohol in the mixed dispersant and the timing of adding sodium carbonate in the examples and comparative examples are summarized in Table 1 below.

[0061] [Table 1]

[0062] Experimental Example 1. Measurement of CPA and bulk density of vinyl chloride polymer The resin slurries produced in the above examples and comparative examples were dehydrated and dried to obtain particulate vinyl chloride polymers. The CPA and bulk density of the obtained vinyl chloride polymers were measured. The CPA was measured according to ASTM D 3367-95, and the bulk density was measured according to ASTM D 1895 Method A, and the results are shown in Table 2 below.

[0063] [Table 2]

[0064] As shown by the above results, it was confirmed that the vinyl chloride polymer of the present invention had the highest CPA among the Examples and Comparative Examples, while maintaining excellent bulk density. This means that the vinyl chloride polymer of the present invention exhibits both excellent mechanical properties and a high melting rate. In particular, it was confirmed from the above results that a vinyl chloride polymer having such a high CPA and excellent bulk density can be produced by setting the content of highly hydrated polyvinyl alcohol in the mixed dispersant at 50-60 wt % and adding a carbonate metal salt before adding the monomer.

[0065] Experimental Example 2. Melting rate measurement 15g of Ca-Zn stabilizer, 21g of chlorinated polyethylene (CPE7000, manufacturer: Weipren), 29g of TiO, and 336g of CaCO were added to 300g of the resin prepared in the above examples and comparative examples, and mixed for 6 minutes using a mixer (manufacturer: HANIL ELECTRIC, product name: HMF-3100S). Then, 56g of the mixture was put into a Brabender plastograph mixer at 165°C and 45 rpm for 6 minutes to measure the melting time. The results are shown in Table 3 below.

[0066] [Table 3]

[0067] As expected from the previous Experimental Example 1, the Example of the present invention had the shortest melting time. This means that the vinyl chloride polymer of the present invention exhibits superior mechanical properties compared to the Comparative Examples. In particular, when Examples 1 to 3 and Comparative Examples 3 to 5, which differ only in the timing of sodium carbonate addition, are compared, it can be seen that the melting time of Comparative Examples 3 to 5, in which sodium carbonate is added after the monomer addition, is longer by about 7 seconds. This confirms that the mechanical properties of the final polymer can change depending on the timing of sodium carbonate, i.e., carbonate metal salt, addition.

[0068] Experimental Example 3. Measurement of vinyl chloride polymer content in the surface layer The resin slurries obtained in the examples and comparative examples were dehydrated and dried to obtain particulate vinyl chloride polymers, and the content of vinyl chloride polymers in the surface layers of the particles was measured. The content was calculated under the following conditions.

[0069] The content of the vinyl chloride polymer in the surface layer was calculated by the following method using XPS analysis: K-ALPHA+ (manufacturer: Thermofisher) was used as the XPS analysis equipment.

[0070] 1) Assume that the only materials that make up the surface of vinyl chloride polymers are PVC, PVA, and PVAc. 2) Using PVC produced by bulk polymerization without using a dispersant, calculate the relative ratio of C element to Cl element in PVC particles (C:Cl=2.17:1). Since PVC produced by bulk polymerization consists of only PVC, the relative ratio calculated above is the relative ratio of C element to Cl element in pure PVC. Next, use the calculated relative ratio to back-calculate the PVC content from the Cl content measured in the surface layer of the target vinyl chloride polymer.

[0071] 3) The content of PVAc is calculated using the specific BE value appearing in the carbonyl peak present in PVAc in the C peak. 4) The C peak remaining after subtracting the contents of PVC and PVAc from the total content is determined to be the PVA content.

[0072] 5) The content of PVC based on the total content of PVC, PVA, and PVAc calculated by the above process (PVC / (PVC+PVA+PVAc))*100% is defined as the content of vinyl chloride polymer. The results are shown in Table 4 below.

[0073] [Table 4]

[0074] Examples 1 to 3 show a higher content of vinyl chloride-based polymer in the surface layer compared to the comparative example, which means that the vinyl chloride-based polymer according to the examples of the present invention has the thinnest skin layer thickness and is more likely to melt.

[0075] Experimental Example 4. Measurement of residual vinyl chloride monomer content The resin slurries obtained in the above examples and comparative examples were dehydrated to a moisture content of about 15%, and then 20 g portions were placed in paper cups (diameter 9 cm, height 12 cm) and dried in an oven at 80°C for 8 hours. They were then placed in vials and the content of the remaining vinyl chloride monomer was measured using HS-GS (Headspace-Gas Chromatography) (measurement conditions: 1 g of resin was sealed in a 20 ml vial and the components of the vinyl chloride monomer released were analyzed at 90°C for 20 minutes). The measurement results are shown in Table 5 below.

[0076] [Table 5]

[0077] As can be seen from the above table, the vinyl chloride polymers prepared in the examples of the present invention have a significantly low residual vinyl chloride monomer content, which means that the vinyl chloride polymers of the present invention are not only excellent in melting rate and mechanical properties, but also have advantages in terms of toxicity compared to vinyl chloride polymers prepared by existing methods.

Claims

1. A step (S1) of introducing a mixed dispersant and a carbonate metal salt into a polymerization reactor; (S2) polymerizing a vinyl chloride monomer in the presence of the mixed dispersant and a carbonate metal salt; Including, The mixed dispersant contains a highly hydrated polyvinyl alcohol having a hydration degree of 80 mol % or more, The content of the highly hydrated polyvinyl alcohol in the mixed dispersant is 50 to 60% by weight.

2. 2. The method for producing a vinyl chloride polymer according to claim 1, wherein the mixed dispersant and the carbonate metal salt are mixed in advance and then charged into a polymerization reactor.

3. The method for producing a vinyl chloride polymer according to claim 1, wherein the mixed dispersant further comprises a low-hydration polyvinyl alcohol having a degree of hydration of less than 80 mol% and a cellulose-based dispersant.

4. The method for producing a vinyl chloride polymer according to claim 3, wherein the cellulose-based dispersant is one or more selected from the group consisting of methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.

5. The carbonate metal salt is sodium carbonate (Na 2 CO 3 ), potassium carbonate (K 2 CO 3 ), and sodium bicarbonate (NaHCO 3 2. The method for producing a vinyl chloride polymer according to claim 1, wherein the vinyl chloride polymer is one or more selected from the group consisting of:

6. 2. The method for producing a vinyl chloride polymer according to claim 1, wherein the mixed dispersant is used in an amount of 0.05 to 0.15 parts by weight based on 100 parts by weight of the vinyl chloride monomer.

7. 2. The method for producing a vinyl chloride polymer according to claim 1, wherein the carbonate metal salt is used in an amount of 0.01 to 0.03 parts by weight based on 100 parts by weight of the vinyl chloride monomer.

8. The method for producing a vinyl chloride polymer according to claim 1, wherein the polymerization is carried out at 50 to 65° C.

9. A vinyl chloride polymer, the content of which in a surface layer is 50% or more as measured by XPS analysis.

10. The vinyl chloride polymer according to claim 9, having a CPA (cold plasticizer absorption) of 18% or more.

11. Bulk density is 0.580 g / cm 3 The vinyl chloride polymer according to claim 9, characterized in that

12. The vinyl chloride polymer according to claim 9, which is in the form of spherical particles.

Citation Information

Patent Citations

  • Preparation of vinyl chloride type polymer emulsion

    JP1980031820A

  • Spherical vinyl polychloride particle

    JP1986204207A

  • Production of bulky high density vinyl resin

    JP1987000504A

  • Skinless porous granular polyvinyl chloride resin and manufacture

    JP1988268706A

  • Bridged porous skinless particle of PVC resin and manufacture

    JP1988268713A